Masterpiece : the art of discipling youth - Martin, Paul (San Diego, California : The Youth Cartel, 2012)
Geared toward church youth workers, this book provides a fresh approach to revealing teenagers "as the masterpieces Christ created them to be".
Includes bibliographical references, pages 141-143.
Keywords: Church work with teenagers; Teenagers -- Religious life; Christian life